Identification of a 14-Gene Prognostic Signature for Diffuse Large B Cell Lymphoma (DLBCL) - Feng, Pengcheng; Li, Hongxia; Pei, Jinhong; Huang, Yan; Li, Guixia (Frontiers in Genetics, 2021)
Immunotherapy is thought as a potential strategy to resist cancers, while this treatment is not always effective for patients suffering from diffuse large B cell lymphoma (DLBCL), because of the inadequate understanding to complex immune microenvironment. Based on the current situation, it is critical to systematically investigate the immune pattern. The immune-related genes (IRGs) expression data of DLBCL patients were downloaded from the GEO database. Univariate and multivariate cox proportional hazards, LASSO regression analysis and Kaplan-Meier survival analysis were used to screen survival-related IRGs and build a prognosis model. Gene enrichment analysis was performed to evaluate the biological functions of survival-related genes. A prognostic signature containing 14 IRGs (AQP9, LMBR1L, FGF20, TANK, CRP, ORM1, JAK1, BACH2, MTCP1, IFITM1, TNFSF10, FGF12, RFX5 and LAP3) was built. This model was validated by external data, and performed well. DLBCL patients were divided into low and high-risk groups, according to the risk scores. Different immune infiltration pattern existed between two groups. The results of CIBERSORT showed that different immune status was observed in these groups. GSEA indicated 12 signaling pathways were significantly enriched in the high-risk group, such as natural killer cell-mediated cytotoxicity, toll-like receptor signaling pathway and so on. In summary, fourteen clinically significant IRGs were screened to build risk score formula. This formula was an accurate tool to guide the prognosis and treatment of DLBCL patients which provided a certain basis for personalized treatment.